NEW APPROACHES TO ORGAN PRESERVATION SURGERY IN PATIENTS WITH LIVER CANCER: A CRITICAL REVIEW AND EVALUATION OF INNOVATIONS - Hamaue, Thomas Richard; Pastorello, Maria Fernanda Burin; Hamaue, Ayumi; Birtche, Luiz Claudio Medeiro; Mello, Gabriel Morgan; Grili, Luigi dos Santos; Bitche, Pedro Henrique Medeiro; Bernardi, Giovanna Souza Lima; Castello Branco, Lucas Charuri de Andrade; Sanfins, Barbara Zorzi (Seven Editora, 2025)
Liver cancer, especially hepatocellular carcinoma, is a leading cause of cancer death and is more common in patients with cirrhosis and chronic hepatitis. Innovative surgical techniques, such as anatomical resection and selective portal embolization, have been shown to be effective in preserving healthy liver tissue and reducing postoperative complications. Studies indicate improvements in survival and recovery rates, especially in cases of tumors located in areas that are difficult to resect. However, implementing these approaches requires expert centers and more research to validate long-term results. DOI: https://doi.org/10.56238/sevened2024.039-022